The 8 dimensions of leadership : DiSC strategies for becoming a better leader - Sugerman, Jeffrey; Scullard, Mark.; Wilhelm, Emma. (San Francisco, CA : Berrett-Koehler Publishers, 2011)
'The 8 Dimensions of Leadership is the first book to explore leadership through the lens of Inscape's third generation DiSC model of human behavior. This title is designed to paint an inclusive picture of the varied approaches that make for strong leadership. It primarily focuses on the interpersonal realm of leadership and helps readers identify which of the eight approaches comes most naturally to them. This book utilizes and explains the DiSC model to help leaders learn to be more effective in their relationships and leadership roles. Focusing on the reader's individual approach to leadership, the authors use primary literature and the latest research to support the third generation DiSIC model, which illustrates where different leadership styles fall on a simple circular map. Readers will be able to identify their own approach to leadership, explore the strengths and challenges that leaders with each of the approaches faces, and discover strategies for more effective leadership based on their personal approach'--
Includes bibliographical references and index.
Keywords: Leadership